Система менеджменту безпеки харчової продукції - Панченко, М. О.; Городецька, Т. Б.; Panchenko, М.; Gorodeckaya, T. (КНТУ, 2014)
У статті обґрунтовується необхідність підвищення якості харчової продукції та рівня її безпеки. Досліджується сукупність факторів, що впливають на підвищення інтересу українських підприємств харчової промисловості до забезпечення безпеки продукції, що випускається. Розглядаються розробка та впровадження системи управління безпекою на харчових підприємствах. The necessity of upgrading food products and its strength security is grounded in the article. The aggregate of factors, influencing on the increase of interest of the Ukrainian enterprises of food retail industry to providing of safety of the produced products, is considered. Development and introduction of control the system by safety is also examined on food enterprises. In the conditions of competition exactly those enterprises win at the food market, whose products will be more high-quality and safe, and also those which quick than other will inculcate the checking of quality of NASSR system in the activity. NASSR is conception, which foresees systematic authentication, estimation and management dangerous factors which substantially influence on safety of products. Practical application of principles of NASSR sets quite a bit positive patterns of achievement of high results on providing of safety of food products etc.
The System of Food Products Safety Management
Keywords: харчова продукція; харчова безпека; якість продукції; food products; food safety; quality of products; system NASSR